Priprava motorja za tekmovalni razred - Bizjan, Frančišek (Strojniški vestnik, 2001)
Motorcycle engines used in the Supersport Class are interesting for engineers who develop new products because of the restrictions imposed by the regulations. These regulations do not allow major changes to the engine and resrict the choice of replacement parts that can be used. Nevertheless, the prepared engines achieve great power and the lessons learned during such an exercise can be put to good use in the development of mass-produced engines. These modified engines are not capable of significantly higher engine speeds, however, they can have a very high mean effective pressure, amongst the highest found in naturally aspirated engines. This article describes the steps involved in modifying an engine as well as our impressions of the importance and the possibilities of computer simulations in such types of racing.
Keywords: kolesa motorna; motorji ZNZ; karakteristike motorjev; programiranje računalniško; motorna kolesa; motorji; karakteristike; predelava